As facetas conceptuais do dêitico você: evidências semântico-gestuais - Sandra Cristina Becker (2009)
The present work aims to contribute to a better understanding of deixisreferenciation. The phenomenon of pointing is contemplated here through theoretical approaches that understand language as a constituting part of human cognition. The canonical viewing of the pronominal você (you) that indicates either a fixed pointing to the hearer or to a generic entity is analyzed through the propositions of many scholars such as Karl Bühler, Ronald Langacker, Johanna Rubba, Susan Goldin-Meadow and David McNeill. The deixis você is put on stage and has its reference scope mapped in oral and written interactions, more specifically in interviews broadcasted in Brazilian television.The process of referenciation via você, as well as its psychological nature, was studied through excerpts of 4 interviews 2 oral and 2 written. As will be shown, textual elements and gesture maneuvers provided some evidence to the emergence of the egocentric, projected, and interlocutory facets. This amounts to saying that você might point to an I, to the third person in singular and plural forms she/he, they or tothe element we. Aiming to confirm the emergence of these facets as well as to identify and map them, a linguistic analysis based on a substitution of você for its acceptions and focusing on TAM (tense, aspect and mood) was carried out together with a gesture investigation. Results converge to suggest that the referenciation scope provided by você is large and complex. This scope reflects the continuous process of gramaticalization of this entity and these new targets constitute a less schematic viewing of this deictic. Optimal viewing arrangements that support the mechanism of cross-world identification postulated by Langacker (1987) indicate that new elements are brought to an imagetic scenario though the process of perpectivation, selection and abstraction. Gesture plays a significant role in these findings since it holds clue to the construction of conceptual spaces. Metaphorical, iconic, beater and deictic gestureswere relevant tools for the identification of the facets mapped. These facets do not constitute discrete entities since they have fussy boundaries and emerge online, as discourse unfolds. They appear in subrogated spaces which have imagetic nature and are produced by the conceptualizer thought specific movements of perspectivation, selection and abstraction.